CORRELATION OF MORAL ORIENTATION AND THE DEVIANT BEHAVIOR PROPENSITIES IN ADOLESCENCE - Dauksha, Liliya Maryanovna (Insight: the psychological dimensions of society, 2019)
The goal of our research was to examine the nature of the correlation of moral orientation and the deviant behavior propensities in adolescence. Methods: “Fairness-Concern” Moral Judgment Preference Questionnaire (S.V. Molchanov, A.I. Podolsky); the deviant behavior propensities of under-aged diagnosing technique (E.V. Leus; A.G. Solovyov). The results of identification of statistically significant differences in the preferred moral judgments of adolescent boys and adolescent girls indicate that adolescent boys are more focused on themselves and their interests. No statistically significant differences in the deviant behavior propensities of adolescent boys and adolescent girls were detected. A positive correlation between the delinquent behavior propensity, the pre-conventional level of moral development (according to L. Kohlberg) and self-concern (according to C. Gilligan and N. Eisenberg) was revealed. No connection between the propensity for delinquent behavior and the post-conventional level of moral development of adolescents was found. The high level of addictive behavior among adolescents is negatively related to the post-conventional level of moral development and self-sacrifice. The high propensity of adolescents to engage in aggressive behavior (such as verbal and physical aggression, hostility, negativity, impudence, and vindictiveness) is associated with the lesser importance of moral judgements, which justify the moral standards by necessity to care for others and protect their rights on the basis of empathy. Negative correlation between the propensity for self-injurious behavior and the moral judgements focused on personal rights and social contact was revealed. Conclusion. The fact of correlation between moral orientation and propensity to deviant behavior in adolescence was revealed. High propensity for addictive, self-injurious, aggressive, delinquent behavior is negatively correlated with the post-conventional level of moral development and self-sacrifice of adolescents.